Neuroprotective Compounds from Salix pseudo-lasiogyne Twigs and Their Anti-Amnesic Effects on Scopolamine-Induced Memory Deficit in Mice - Yang, Heejung; Lee, Sang Hoon; Sung, Sang Hyun; Kim, Jinwoong; Kim, Young Choong (Planta Medica, 2013)
Bioassay-guided fractionation of an 80 % methanolic extract of Salix pseudo-lasiogyne twigs has resulted in the isolation of two new compounds (1–2) along with ten known ones (3–12). The new compounds were determined to be 3′-O-acetylsalicin (1) and 2′,6′-O-acetylsalicortin (2) by using spectroscopic analyses. Compounds (3–12) were identified as salicin (3), 2′-O-acetylsalicin (4), salicortin (5), 2′-O-acetylsalicortin (6), 3′-O-acetylsalicortin (7), 6′-O-acetylsalicortin (8), 2′-O-(E)-ρ-coumaroylsalicortin (9), grandidentatin (10), isograndidentatin (11), and saligenin (12). Among the isolated compounds, compounds 2, 5, 6, 7, and 8 bearing 1-hydroxy-6-oxo-2-cyclohexenecarboxylate moiety significantly inhibited lipopolysaccharide-induced nitric oxide production in BV2 microglial cells in vitro. Further, we studied anti-amnesic activities of the 80 % methanolic extract, the EtOAc fraction, and compound 6 from S. pseudo-lasiogyne. They exerted a significant cognitive-enhancing effect on scopolamine-induced memory deficit in mice. In addition, they also significantly increased the reduced activities of glutathione reductase and superoxide dismutase and the glutathione content in the hippocampus and cortex of scopolamine-induced amnesic mice.
Keywords: Salix pseudo-lasiogyne; Salicaceae; salicortin; 1-hydroxy-6-oxo-2-cyclohexenecarboxylate; BV2 microglial cell; passive avoidance test